The Effect of Perception, Knowledge, and Socialization of Tax Rate Changes on MSME Taxpayer Compliance with Tax Sanctions as a Moderating Variable - Cantika Sweca Sariani; Gede Adi Yuniarta; Sunitha Devi (Lembaga Riset Ilmiah, 2026)
Tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia remains relatively low despite the continuous growth in the number of MSMEs and the government's policy of reducing the Final Income Tax rate to 0.5% to encourage voluntary compliance. Previous studies have generally examined the effects of tax knowledge, tax socialization, and tax rates on taxpayer compliance separately, resulting in inconsistent findings and limited understanding of the role of tax sanctions in strengthening these relationships. Therefore, this study aims to analyze the influence of tax knowledge, tax socialization, and taxpayer perceptions of changes in the Final Income Tax rate on MSME taxpayer compliance, as well as to examine the moderating role of tax sanctions. This research employs a quantitative explanatory approach using survey data collected from 400 MSME taxpayers in Denpasar City. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that tax knowledge, tax socialization, and perceptions of the Final Income Tax rate positively and significantly influence taxpayer compliance. Tax sanctions do not moderate the relationship between tax knowledge and compliance, but they strengthen the effects of tax socialization and tax rate perceptions on compliance. These findings suggest that MSME tax compliance is shaped by a combination of internal factors, external educational efforts, and law enforcement mechanisms. The novelty of this study lies in the integration of tax sanctions as a moderating variable in the relationship between tax knowledge, tax socialization, tax rate perceptions, and taxpayer compliance within the context of MSMEs following the implementation of the 0.5% Final Income Tax policy. The findings contribute to the development of tax compliance behavior literature based on the Theory of Planned Behavior and provide practical insights for policymakers to enhance compliance through tax education, digital socialization programs, and consistent enforcement of tax sanctions.